Pushing pixels secret weapons for the modern Flash animator - Georgenes, Chris (Focal Press, 2013)
"You've got the cheats, tutorials, and how-tos. What else do you need? Go above and beyond those stop-gaps and step-by-steps with Pushing Pixels, the real-world guide to developing dynamic and fun content from conception to deployment. Whether you are animating for a short, a fun cartoon, or a mobile game, renowned Flash expert Chris Georgenes will show you his approach with various types of animation projects, from start to finish. Providing in-depth knowledge of the little-known secrets used by the pros to produce creative, professional animations, this is the go-to source for anyone looking to create great animation"--Provided by publisher.